2021
DOI: 10.18203/2320-1770.ijrcog20212963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional Papanicolaou smear and liquid‑based cytology: a study of cervical cancer screening at a tertiary care center in Bengaluru

Abstract: Background: Cervical cancer is the fourth commonest cancer affecting women worldwide and the second most common cancer in women aged 15-44 years. The Papanicolaou (Pap) smear has been the cornerstone of screening for cervical neoplasm for the last 50 years. Liquid-based cytology (LBC) was introduced in mid-1990s as an alternative technique to process cervical samples has many benefits over Pap. A new second generation technique, Liquiprep was introduced after a decade has the advantage of a much lower cost. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study published by Phaliwong et al in 2018 on 28,564 cases showed that the percentage of unsatisfactory Pap smears was significantly higher than LBC (52.3% vs. 40.5%) [ 36 ]. The opinion suggesting the need for the extensive use of LBC in CC screening instead of a Pap smear is very well established in the literature [ 37 , 38 , 39 , 40 ]. In contrast, there is no evidence to explain that LBC differs from Pap smear in their accuracy in detecting CIN2+ lesions [ 41 ].…”
Section: Review Resultsmentioning
confidence: 99%
“…A study published by Phaliwong et al in 2018 on 28,564 cases showed that the percentage of unsatisfactory Pap smears was significantly higher than LBC (52.3% vs. 40.5%) [ 36 ]. The opinion suggesting the need for the extensive use of LBC in CC screening instead of a Pap smear is very well established in the literature [ 37 , 38 , 39 , 40 ]. In contrast, there is no evidence to explain that LBC differs from Pap smear in their accuracy in detecting CIN2+ lesions [ 41 ].…”
Section: Review Resultsmentioning
confidence: 99%